Comparison among Different Screening Tests for Diagnosis of Adolescent Hypertension. (20th June 2013) - Totaro, Silvia; Rabbia, Franco; Rabbone, Ivana; Covella, Michele; Berra, Elena; Fulcheri, Chiara; Di Monaco, Silvia; Testa, Elisa; Veglio, Franco
Abstract : The diagnosis of childhood hypertension based upon percentile tables proposed by the international guidelines is complex and often a cause of underdiagnosis, particularly among physicians who have not had specific training in the field of adolescent hypertension. The use of a simple and accurate screening test may improve hypertension diagnosis in adolescents. The aim of our study is to compare the different screening methods currently used in the literature to improve the diagnosis of childhood hypertension. We have conducted a cross-sectional population-based study of 1412 Caucasian adolescents among students of public junior high schools of Turin, Italy. In this population we have defined the hypertensive status with four different screening tests: BPHR, Somu's equations, Ardissino, and Kaelber methods. Finally, we compared the diagnostic accuracy of the 4 screening tests with the gold standard. Our analysis identifies in BPHR the test which combines ease of use and diagnostic accuracy.